A Novel Entry/Uncoating Assay Reveals the Presence of at Least Two Species of Viral Capsids During Synchronized HIV-1 Infection. - Claire Da Silva Santos; Kevin Tartour; Andrea Cimarelli (PLoS Pathogens, 2016)
To better characterize the behavior of HIV-1 capsids we developed EURT, for Entry/Uncoating assay based on core-packaged RNA availability and Translation. EURT is an alternative to Blam-Vpr, but as reporter RNA translation relies on core opening, it can be used to study viral capsids behavior. Our study reveals the existence of two major capsid species, a dead end one in which the viral genome is readily exposed to the cytoplasm and a functional one in which such exposure requires artificial core destabilization. Although reverse transcription drives a faster loss of susceptibility of viral cores to high doses of PF74, it does not lead to higher exposure of the viral genome, implying that viral cores protect the genome irrespectively of reverse transcription. Lastly, IFNα drifts cores from functional to non-functional species, revealing a novel core-destabilizing activity. This assay sheds new light on the behavior of viral cores inside target cells.